The synergy between artificial intelligence and experiential learning in enhancing students’ creativity through motivation - Murniarti, Erni; Siahaan, Goklas (Frontiers in Education, 2025)
IntroductionThis study explores how the synergy between Artificial Intelligence (AI) and Experiential Learning enhances students’ creativity through motivation.MethodsA quantitative survey with 200 purposively selected students was conducted. A structured questionnaire was used to collect data on AI usage, motivation, and creativity.ResultsAI integrated with experiential learning significantly boosts motivation, which in turn increases creativity.DiscussionThe findings support incorporating AI-based experiential practices in education to foster student innovation and engagement.